Enhancing weed control in imidazolinone-resistant corn and soybean strip intercropping systems through tank mixtures of imidazolinone and residual herbicides - Yi Ru; Xiangxin Zhuang; Lingyang Feng; Hongyou Wan; Jialin Yu (Crop Protection, 2026)

Non-nutritive sweeteners in hand-shaken beverages: Occurrence, consumption patterns, and dietary risk assessment - Yu-Chia Yeh; Wan-Ru Li; Yu-Syuan Luo (Food Research International, 2026)

Stage-dependent pre-assessment of formaldehyde release from medium-density fiberboard under indoor environmental conditions - Xinying Ru; Hui Wan; Maoxu Wang; Mengxia Yin (Building and Environment, 2026)

High-throughput toxicological profiling and ToxPi-based prioritization of chemical migrants from recycled paper used in food contact materials - Pei-Shan Chih; Pei-Chun Hsu; Rachelle D. Arcega; Wei-Hsiang Chang; Pei-Chu Tai; Ching-Chang Lee; Trias Mahmudiono; Wan-Ru Wang; Rong-Jane Chen; Hsiu-Ling Chen (Journal of Hazardous Materials, 2026)

Paedocin A: An undescribed iridoid with a C1-C4 ether linkage from Paederia foetida with hepatoprotective effects - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry Letters, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

LncRNA WFDC21P mediates the tobacco carcinogen induced malignant transformation of human normal lung epithelial cells by regulating tumor stemness - Shengsheng Li; Ru Liu; Shiyao Ye; Yitong Li; Linhan Huang; Qiuxian Wan; Zhuolin Liu; Yibo Wu; Nuoyan Wang; Minmin Huang; Jianjun Wu (Food and Chemical Toxicology, 2026)

Comprehensive metabolic programming by enzymatic nanovesicle for acute kidney injury therapy - Yao Lei; Yuzhu Wu; Chao Li; Canwei Zou; Mingchuan Mao; Wan-Ru Zhuang; Yun Qu; Jiaqi He; Chao Liang; Weidong Nie; Hai-Yan Xie (Science Bulletin, 2026)

Deep carbon cycling in continental subduction zones - Sheng-Ao Liu; Wan-Yu Sun; Yuan-Ru Qu; Hong-Li Yang (Lithos, 2026)

Non-enzymatic electrochemical determination of the food-related biogenic amine serotonin using a reduced graphene oxide/organic–inorganic Copper(I) phosphate composite - Asit Kumar Panda; Tzu-Yuan Sung; Wan-Ju Lu; Yi-Ru Cheng; Wen-Hui Fang; Chih-Min Wang (Food Bioscience, 2026)

Mask-CDKD: A source-free and label-free cross-domain knowledge distillation framework from SAM for satellite onboard VHR land-cover mapping - Daoyu Shu; Zhan Zhang; Xiao Huang; Ru Wang; Nan Jia; Xinzhe Fu; Bingnan Yang; Fang Wan; Jianzhong Lu; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Constructing an in-situ Fenton reaction using iron-air fuel cells with a graphite cathode for landfill leachate treatment - Sizhuo Wan; Cong Ding; Bingyin Liu; Mahmood Qaisar; Bibi Saima Zeb; Ru Wang; Linjiang Yuan (ENGINEERING Environment, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Multifunctional carboxymethyl cellulose/polydopamine dual-network conductive hydrogels for motion detection and photothermal therapy - Yiying Wei; Bo Cong; Xiaopu Ji; Dangyang Wang; Jinghui Hu; Zonglei Mou; Haiqing Song; Yue Zhi; Yushu Liu; Guofeng Zhang; Wan Ru Sun; Pingyu Wang; et al. (Carbohydrate Polymers, 2026)

Remote impacts of maritime continent deforestation on early summer precipitation across Asia - Chiung-Wen June Chang; Wan‑Ru Huang; Yi-Chieh Chen; Suranjith Bandara Koralegedara (Climatic Change, 2026)
Deforestation in the Indo-Pacific Maritime Continent (MC) has intensified in recent decades, yet its remote impacts on Asian monsoon precipitation remain inadequately understood. Using idealized land-use perturbation experiments with the Community Earth System Model, we demonstrate that MC deforestation reorganizes early-summer (May–June) precipitation across Asia through large-scale circulation changes. Our results show that Meiyu precipitation, the early-summer rainy season along the subtropical East Asian coastal zone (SEAC), is suppressed by strengthened subsidence and column drying, whereas precipitation over the Indian Peninsula increases under enhanced ascent and vertically integrated moisture-flux convergence. Precipitation characteristics also shift regionally: the SEAC exhibits simultaneous reductions in both frequency and intensity, the Indian Peninsula shows increases in both metrics, and the MC itself experiences fewer but more intense events. A joint frequency–intensity analysis reveals that these precipitation patterns reflect regional thermodynamic and dynamic controls, where reduced near-surface humidity and equivalent potential temperature suppress event initiation, while elevated values facilitate initiation, and variations in column moisture and moisture-flux convergence regulate precipitation intensity. Collectively, these results identify a land-use–driven teleconnection through which localized deforestation in the MC remotely modulates regional circulation and Meiyu precipitation, highlighting the central role of tropical land–atmosphere coupling in shaping Asian hydroclimate variability.

Protist‐Bacteria Trophic Interactions Contribute to Higher Community Stability in Subsoils Than Topsoils - Suo Liu; Jingyi Ru; Sihang Deng; Jiesi Lei; Zhencheng Ye; Yu Tang; Changchun Zhai; Shiqiang Wan; Yunfeng Yang (Global Change Biology, 2026)
Climate change is reshaping ecosystem components and functions across soil profiles. In this study, we examined the effects of altered precipitation and nighttime warming on soil microbial communities in both topsoils (0–20 cm in depth) and subsoils (20–50 cm in depth) in a long‐term field experiment in Inner Mongolia, China. Unexpectedly, moisture, belowground net primary production, and NO 3 − content in subsoils were all affected more by climate changes than topsoils. Moreover, using multiple resistance metrics, including α‐diversity, β‐diversity, microbial network complexity, and network robustness, we found that both bacterial and protistan communities in subsoils exhibited greater resistance to climate change than those in topsoils, while fungal communities showed no consistent pattern. Enhanced bacterial resistance in subsoils was associated with lower 16S rRNA gene operon ( rrn ) copy number, reduced GC content, lower genome and cell size, and other oligotrophic traits, collectively supporting adaptation to nutrient‐poor and stressful environments. Protistan resistance in subsoils tracked bacterial resistance and was reinforced by stronger trophic interactions and functional traits such as protective shells, greater motility, and reduced cell size, reflecting a bottom‐up control, as soil protists are primarily phagotrophs shaped by bacterial prey supply. Abundant bacteria enhanced resistance through oligotrophic adaptations and positive intra‐community interactions, while abundant protists reduced resistance, potentially due to the dominance of negative intra‐community interactions. Partial least squares analyses revealed that microbial community resistance modulated soil heterotrophic respiration (R h ), connecting community resistance to carbon cycling. Together, these findings demonstrate that the often‐overlooked resistance of subsoil microbiomes could buffer ecosystem functions under future climate conditions, suggesting that traits (e.g., rrn copy number) and trophic interactions can outweigh diversity for community stability.

Cyclopentanoid monoterpene glycosides from the aerial parts of Paederia foetida L - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry, 2026)

Preparation of indicator cards for freshness detection of rice with four different processing degrees during storage based on olfactory visualization technology - Wan-ru Liu; Yang Yang; Yue Xu; Bing Wang; Guang Zhang; Xin-yu Xu; Yuan-yuan Wang; Chun-min Ma; Na Zhang (Food Chemistry, 2026)

Association between magnesium sulfate administration and mortality in critically ill patients with sepsis-associated acute kidney injury: a retrospective propensity score-matched cohort study - Xiang-Jie Duan; Jing-Ru Lan; Ming-Gao Zhu; Jin-Lian Chen; Chang-Yun Zhang; Hai-Yan Yin; Wan-Jie Gu (European Journal of Clinical Pharmacology, 2026)

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Conductive forward osmosis membranes modified with rGO-ZnO composites for improving aquaculture wastewater reclamation - Yi-Li Lin; Nai-Yun Zheng; Wan-Ru Tsai (Journal of Water Process Engineering, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Effects of nighttime warming and nitrogen addition on phytoplankton biomass in a submerged macrophytes-dominated freshwater wetland - Yaru Lyu; Jiayin Feng; Wenjing Ma; Chao Wang; Mengyu Yan; Zixuan Yang; Yunpeng Guo; Jinhua Zhang; Hongpeng Wang; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Journal of Environmental Sciences, 2026)

Anti-diabetic properties of yellowfin tuna protein hydrolysates and identification and screening of novel anti-diabetic peptides against α-amylase and DPP-IV - Xiangtan Zhao; Peng Wan; Deke Chen; Bingna Cai; Hua Chen; Jun Li; Si Li; Ailing Duan; Ru Li; Si Zhang; Jianyu Pan (Food Chemistry, 2026)

Seasonal and spatial variation, and land-use influences on riverine microplastics and their ecological risks in the Yanshui River Basin - Yi-Wei Biao; Hong-Ming Zheng; Wan-Ru Chen (Journal of Environmental Chemical Engineering, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

Freeze–thaw durability and environmental risk assessment of silty soil improved using EICP combined with magnesite tailings powder - Hua Yuan; Shuaiqi Wang; Ziqi Zhu; Mengyao Ru; Aochong Wan; Xiang Zhu (Environmental Research, 2025)

Inspired by traditional printing pastes: Green eco-design of phytic acid-modified starch and durable flame-retardant cellulose-based fabrics - Wan-Meng Song; Bao-Hong Wang; Ru-Yu Fan; Yun Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Portable surface-enhanced Raman scattering platform for rapid identification of nanoplastics at single-particle level - Li-Chia Lu; Wan-Ru Chen; Chia-Ling Kuo; Dehui Wan (Journal of Hazardous Materials, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

Cross-view geo-localization with panoramic street-view and VHR satellite imagery in decentrality settings - Panwang Xia; Lei Yu; Yi Wan; Qiong Wu; Peiqi Chen; Liheng Zhong; Yongxiang Yao; Dong Wei; Xinyi Liu; Lixiang Ru; Yingying Zhang; Jiangwei Lao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A programmed Ca2+ nanomodulator by dynamically regulating autophagy and neuroinflammation for Parkinson's disease therapy - Wengui Lu; Chuan Zhang; Yaru Zhang; Ru Xiao; Chaoqi Wei; Fan Zhang; Zhenbao Li; Hewan Xia; Mimi Wan; Zhifei Cheng; Qi Wang (Chemical Engineering Journal, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Different responses of phytoplankton taxa to water N and P inputs in a freshwater wetland: A mesocosm study - Wenjing Ma; Jiayin Feng; Jinhua Zhang; Hongpeng Wang; Yunpeng Guo; Yaru Lyu; Chao Wang; Zixuan Yang; Mengyu Yan; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Marine Pollution Bulletin, 2025)

Critical role of pH in wastewater treatment and resource recovery from the hazardous chemical polishing wastewater - Sizhuo Wan; Sifan Wang; Mahmood Qaisar; Bibi Saima Zeb; Ru Wang; Linjiang Yuan; Ping Zheng (Journal of Water Process Engineering, 2025)

Phosphate recovery from digested wastewater using electrochemical reactors: Trade-off between efficiency and stability - Sizhuo Wan; Ru Wang; Bibi Saima Zeb; Mahmood Qaisar; Linjiang Yuan; Ping Zheng (Desalination, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Associations between lifestyle factors, physiological conditions, and epigenetic age acceleration in an Asian population - Yu-Ru Wu; Wan-Yu Lin (Biogerontology, 2025)
Epigenetic clocks use DNA methylation (DNAm) levels to predict an individual’s biological age. However, relationships between lifestyle/biomarkers and epigenetic age acceleration (EAA) in Asian populations remain unknown. We here explored associations between lifestyle factors, physiological conditions, and epigenetic markers, including HannumEAA, IEAA, PhenoEAA, GrimEAA, DunedinPACE, DNAm-based smoking pack-years (DNAmPACKYRS), and DNAm plasminogen activator inhibitor 1 level (DNAmPAI1). A total of 2474 Taiwan Biobank (TWB) individuals aged between 30 and 70 provided physical health examinations, lifestyle questionnaire surveys, and blood and urine samples. Partial correlation analysis (while adjusting for chronological age, smoking, and drinking status) demonstrated that 29 factors were significantly correlated with at least one epigenetic marker (Pearson’s correlation coefficient | r |> 0.15). Subsequently, by exploring the model with the smallest Akaike information criterion (AIC), we identified the best model for each epigenetic marker. As a DNAm-based marker demonstrated to predict healthspan and lifespan with greater accuracy, GrimEAA was also found to be better explained by lifestyle factors and physiological conditions. Totally 15 factors explained 44.7% variability in GrimEAA, including sex, body mass index (BMI), waist-hip ratio (WHR), smoking, hemoglobin A1c (HbA1c), high-density lipoprotein cholesterol (HDL-C), creatinine, uric acid, gamma-glutamyl transferase (GGT), hemoglobin, and five cell-type proportions. In summary, smoking, elevated HbA1c, BMI, WHR, GGT, and uric acid were associated with more than one kind of EAA. At the same time, higher HDL-C and hemoglobin were related to epigenetic age deceleration (EAD). These findings offer valuable insights into biological aging.

Unveiling the role of aeration tanks in the emission and enrichment of airborne antibiotic resistance genes in a wastewater treatment plant - Jui-Hung Yen; Jun-Fa Yeh; Chih-Yu Chan; Hsin-Hsin Tung; Kai-Hsien Chi; Hsin-Chang Chen; Wan-Ru Chen; Charles C.-K. Chou; Ta-Chih Hsiao (Water Research, 2025)

Seasonal variation of diurnal rainfall characteristics over Vietnam - Wan-Ru Huang; Hai Bui-Manh; Tzu-Yang Chiang; Suranjith Bandara Koralegedara (Science of The Total Environment, 2025)

Dissimilatory nitrate reduction to ammonium driven by different electron donors: Mechanisms, recent advances, and future perspectives - Wan-Ru Wen; Tian-Chen Liu; Sheng-Qiang Fan; Xin Tan; Yang Lu; De-Feng Xing; Bing-Feng Liu; Nan-Qi Ren; Guo-Jun Xie (Chemical Engineering Journal, 2025)

Astragalus polysaccharide/carboxymethyl chitosan/sodium alginate based electroconductive hydrogels for diabetic wound healing and muscle function assessment - Letian Tang; Shuyang Xie; Danyang Wang; Yiying Wei; Xiaopu Ji; Yicheng Wang; Nana Zhao; Zonglei Mou; Baoping Li; Wan Ru Sun; Ping Yu Wang; Nicola Paccione Basmadji; et al. (Carbohydrate Polymers, 2025)

Environmentally-Relevant Concentrations of Atrazine Had Minor Impacts on Gut Microbiota and Liver Metabolite in Juvenile Turtles - Huo-Bin Tang; Xin-Ru Qian; Wan-Qiu Yang; Jia-Meng Yang; Jin-Hui Zhang; Hong-Liang Lu (Archives of Environmental Contamination and Toxicology, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Design and experimental analysis of real-time detection system for The seeding accuracy of rice pneumatic seed metering device based on the improved YOLOv5n - He Xing; Yikai Wan; Peng Zhong; Junjiang Lin; Mingtao Huang; Ru Yang; Ying Zang (Computers and Electronics in Agriculture, 2024)

Advanced growing-season precipitation peak promotes soil nitrogen mineralization in a semi-arid grassland - Jiayin Feng; Xiaojing Yue; Benqing Li; Jingyi Ru; Zhenxing Zhou; Lingjie Kong; Jiajun Zhang; Jiaxin Zhou; Guilin Zhou; Wenjing Ma; Yaru Lyu; Jian Song; et al. (CATENA, 2024)

Emergency control of dinoflagellate bloom in freshwater with chlorine enhanced by solar radiation: Efficiency and mechanism - Ru Wang; Ya Cheng; Qiqi Wan; Ruihua Cao; Jie Cai; Tinglin Huang; Gang Wen (Water Research, 2024)

Changes in plant litter and root carbon inputs alter soil respiration in three different forests of a climate transitional region - Jiayin Feng; Chunyu Wang; Jingjing Gao; Huixia Ma; Zheng Li; Yuanfeng Hao; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (Agricultural and Forest Meteorology, 2024)

Bi2O3/Bi@CSs achieved by shock-type heating for fast and long-lasting sodium ion battery - Ya Ru Pei; Xue Jing Yang; Wu Bin Wan; Hai Ming Huang; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2024)

Improved prediction of swimming talent through random forest analysis of anthropometric and physiological phenotypes - Cheng Liu; Bingxiang Xu; Kang Wan; Qin Sun; Ruwen Wang; Yue Feng; Hui Shao; Tiemin Liu; Ru Wang (Phenomics, 2024)

HER2 mutations in advanced cervical neuroendocrine carcinoma: implications for trastuzumab deruxtecan therapy - Wan-Ru Chao; Ming-Yung Lee; Gwo-Tarng Sheu; Yi-Ju Lee; Huang-Pin Shen; Chih-Ping Han (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Enhancing vitamin D3 bioaccessibility: Unveiling hydrophobic interactions in soybean protein isolate and vitamin D3 binding via an infant in vitro digestion model - Jia-Rong Huang; Jing-Ru Song; Wan-Shuang Cai; Zhen-Wen Shao; Da-Yong Zhou; Liang Song (Food Chemistry, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Additive effects of N addition and changing precipitation on soil respiration in a climate transitional forest - Jiayin Feng; Jingjing Gao; Huixia Ma; Chunyu Wang; Yuanfeng Hao; Zheng Li; Jingru Zou; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (CATENA, 2024)

Determination of operation parameters for magnesium-air fuel cell to recover nitrogen and phosphorus from wastewater - Xingze Li; Sizhuo Wan; Tingting Dong; Zhiguo Zhao; Ru Wang (Journal of Environmental Management, 2024)

Effect of heating treatment on processing characteristics of rice dough - Wan-ru Liu; Chun-min Ma; Yang Yang; Bing Wang; Xiao-fei Liu; Yan Wang; Xin Bian; Xiao-xue Guo; Guang Zhang; Na Zhang (Innovative Food Science & Emerging Technologies, 2024)

Distinct response patterns of soil micro-eukaryotic communities to early-season and late-season precipitation in a semiarid grassland - Yanyan Yu; Jingyi Ru; Binghai Lei; Shijie Han; Shiqiang Wan; Junqiang Zheng (Soil Biology and Biochemistry, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Aconitum coreanum and processed products on its base prevent stroke via the PI3K/Akt and KEAP1/NRF2 in the in vivo study - Wan-ting Zeng; Li-ting Zhou; Ru Jia; Yue Liu; Qian Cai; Yang Qu (Metabolic Brain Disease, 2024)

Nighttime warming and nitrogen addition effects on the microclimate of a freshwater wetland dominated by Phragmites australis - Yunpeng Guo; Jian Song; Jiayin Feng; Hongpeng Wang; Jinhua Zhang; Jingyi Ru; Xiaopan Wang; Xu Han; Huixia Ma; Yaru Lyu; Wenjing Ma; Chao Wang; et al. (Science of The Total Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Nitrogen addition does not alter symmetric responses of soil respiration to changing precipitation in a semi-arid grassland - Lingjie Kong; Jian Song; Jingyi Ru; Jiayin Feng; Jiawei Hou; Xueke Wang; Qingshan Zhang; Haidao Wang; Xiaojing Yue; Zhenxing Zhou; Dasheng Sun; Jiajia Zhang; et al. (Science of The Total Environment, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Factors affecting the occurrence and accumulation of perfluoroalkyl acids in indoor dust in Tainan, Taiwan - Yi-Wei Biao; Jing-Ya Xu; Wan-Ru Chen (Chemosphere, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Electrochemically mediated phosphorus and energy recovery from digested effluent - Ling-ling Lai; Si-zhuo Wan; Mahmood Qaisar; Yi-fan Yang; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2024)

Topology optimization on periodic pile barriers considering material damping based on complex band diagrams - Peng Zhou; Shui Wan; Xiao Wang; Aiming Song; Ru Yue (Computers and Geotechnics, 2023)

Deep insights into the population shift of n-DAMO and Anammox in granular sludge: From sidestream to mainstream - Sheng-Qiang Fan; Wan-Ru Wen; Guo-Jun Xie; Yang Lu; Bing-Feng Liu; De-Feng Xing; Jun Ma; Nan-Qi Ren (Water Research, 2023)

Reduction of pesticides and bacteria on Napa cabbage by ozone microbubble water - Hsiu-Ling Chen; Rachelle D. Arcega; Pei-Yu Liao; Chih-Yao Hou; Wen-Chun Liu; Yun-Ru Chen; Jong-Shinn Wu; Wan-Ru Wang; Chia-Min Lin (Postharvest Biology and Technology, 2023)

Biosorption and biotransformation behaviours of veterinary antibiotics under aerobic livestock wastewater treatment processes - Chih-Hung Chen; Yi-Chu Chiou; Chao-Lung Yang; Jen-Hung Wang; Wan-Ru Chen; Liang-Ming Whang (Chemosphere, 2023)

Permeability decides the effect of antibiotics on sedimentary nitrogen removal in Jiulong River Estuary - Ru Wan; Lianghao Ge; Bin Chen; Jin-Ming Tang; Ehui Tan; Wenbin Zou; Li Tian; Meng Li; Zongbao Liu; Lijun Hou; Guoyu Yin; Shuh-Ji Kao (Water Research, 2023)

Inhibition of ecdysone receptor (DcEcR) and ultraspiracle (DcUSP) expression in Diaphorina citri increased susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Xi Wang; Yu-Jing Wei; Ling Zhong; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Facile synthesis of CuFe2O4 catalyst by the electrospinning method to produce hydrogen via the water gas shift of waste-derived syngas - Kyung-Won Jeon; Ji-Woo Park; Ru-Ri Lee; Ji-Hyeon Gong; Won-Jun Jang; Jae-Oh Shim; Young-Wan Ju (Journal of Environmental Chemical Engineering, 2023)

Seasonal changes in diurnal rainfall over Sri Lanka and possible mechanisms - Wan-Ru Huang; Suranjith Bandara Koralegedara; Po-Han Tung; Tzu-Yang Chiang (Atmospheric Research, 2023)

Characteristics and driving factors of abandoned cultivated land in the hilly regions of southern China: A case study in Longnan, Jiangxi Province - Ze-bin Chen; Yong-lin Chen; Chao-jun Li; Jian-ping Lin; Pei-ru Chen; Wei-wei Sun; Zhi-wei Wan (Journal of Mountain Science, 2023)

The loss of Halloween gene function seriously affects the development and reproduction of Diaphorina citri (Hemiptera: Liviidae) and increases its susceptibility to pesticides - Cong Zhang; Bin Wan; Meng-Ru Jin; Jing Wang; Tian-Rong Xin; Zhi-Wen Zou; Bin Xia (Pesticide Biochemistry and Physiology, 2023)

When things get MESI: The Manipulation Experiments Synthesis Initiative—A coordinated effort to synthesize terrestrial global change experiments - Kevin Van Sundert; Sebastian Leuzinger; Martin K.‐F. Bader; Scott X. Chang; Martin G. De Kauwe; Jeffrey S. Dukes; J. Adam Langley; Zilong Ma; Bertold Mariën; Simon Reynaert; Jingyi Ru; Jian Song; et al. (Global Change Biology, 2023)
Responses of the terrestrial biosphere to rapidly changing environmental conditions are a major source of uncertainty in climate projections. In an effort to reduce this uncertainty, a wide range of global change experiments have been conducted that mimic future conditions in terrestrial ecosystems, manipulating CO 2 , temperature, and nutrient and water availability. Syntheses of results across experiments provide a more general sense of ecosystem responses to global change, and help to discern the influence of background conditions such as climate and vegetation type in determining global change responses. Several independent syntheses of published data have yielded distinct databases for specific objectives. Such parallel, uncoordinated initiatives carry the risk of producing redundant data collection efforts and have led to contrasting outcomes without clarifying the underlying reason for divergence. These problems could be avoided by creating a publicly available, updatable, curated database. Here, we report on a global effort to collect and curate 57,089 treatment responses across 3644 manipulation experiments at 1145 sites, simulating elevated CO 2 , warming, nutrient addition, and precipitation changes. In the resulting Manipulation Experiments Synthesis Initiative (MESI) database, effects of experimental global change drivers on carbon and nutrient cycles are included, as well as ancillary data such as background climate, vegetation type, treatment magnitude, duration, and, unique to our database, measured soil properties. Our analysis of the database indicates that most experiments are short term (one or few growing seasons), conducted in the USA, Europe, or China, and that the most abundantly reported variable is aboveground biomass. We provide the most comprehensive multifactor global change database to date, enabling the research community to tackle open research questions, vital to global policymaking. The MESI database, freely accessible at doi.org/10.5281/zenodo.7153253 , opens new avenues for model evaluation and synthesis‐based understanding of how global change affects terrestrial biomes. We welcome contributions to the database on GitHub.

Overcompensation of ecosystem productivity following sustained extreme drought in a semiarid grassland - Jingyi Ru; Shiqiang Wan; Dafeng Hui; Jian Song (Ecology, 2023)
Drought events are projected to be more extreme and frequent in the future and have profound influences on the structure and functions of terrestrial ecosystems. Thus, better understanding the mechanisms of recovery is critical for predicting the future dynamics of terrestrial ecosystems. We performed a 7‐year field precipitation experiment to examine recovery of a grassland ecosystem from different magnitudes of sustained drought, from slight to extreme. The ecosystem was exposed to precipitation treatments in the first 3 years (2010–2012) and recovered during the last 4 years (2013–2016) without precipitation treatments. Overall, large reductions of aboveground net primary productivity (ANPP, −43.3%) and perennial forb biomass (−83.1%) were observed in the third year (2012) of extreme drought only. Nevertheless, ANPP fully recovered within 1 year after the drought treatments were terminated, and the rapid recovery was mainly due to increased soil total nitrogen and root biomass allocation after drought. Surprisingly, large increases of ANPP under the extreme drought treatment occurred during the recovery periods from 2013 to 2015 (+74.1, +88.5, and +119.8 g m −2 year −1 ) compared to the control. The overcompensation offset the extreme drought‐induced reduction of ANPP in the treatment years and was primarily ascribed to the enhanced biomass of perennial grasses (PG). Higher resistance to drought and fast resource acquisition strategy might drive the rapid recovery and expansion of PG. Our findings revealed the rapid recovery of grasslands and the critical role of community overcompensation in maintaining grassland ecosystem function and stability under future climate change scenarios.

Condition optimization of iron-air fuel cell to treat phosphate-containing wastewater regarding sustainable development - Ling-ling Lai; Chao Liu; Meng-yu Liu; Si-zhuo Wan; Zhi-guo Zhao; Ru Wang; Lin-jiang Yuan (Chemosphere, 2023)

Performance optimizing and entropy generation analysis of a platinum–stainless-steel segmented microreactor - Yueh-Heng Li; Hsiao-Hsuan Kao; Yan-Ru Wang; Jianlong Wan; Kanit Manatura (Chemical Engineering Journal, 2023)

Comparison of biochemical composition, nutritional quality, and metals concentrations between males and females of three different Crassostrea sp. - Yanping Qin; Ru Li; Qingliang Liao; Gongpengyang Shi; Yinyin Zhou; Weitao Wan; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Food Chemistry, 2023)

Antimicrobial peptide hepcidin contributes to restoration of the intestinal flora after Aeromonas hydrophila infection in Acrossocheilus fasciatus - Qun-Yin Zhu; Ru-Yi Chen; Jing Yu; Guo-Hua Ding; Rachel Wan Xin Seah; Jie Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Transcriptome‐based analyses of adaptive divergence between two closely related spruce species on the Qinghai–Tibet plateau and adjacent regions - Shuo Feng; Wei Wan; Yang Li; DongLei Wang; Guangpeng Ren; Tao Ma; Dafu Ru (Molecular Ecology, 2023)
Speciation among populations connected by gene flow is driven by adaptation to different environments, but underlying gene–environment associations remain largely unknown. Here, 162 individuals from 32 populations were sampled to obtain 191,648 independent single nucleotide polymorphisms (SNPs) across the genomes of two closely related spruce species, Picea asperata and Picea crassifolia , which occur on the Qinghai–Tibet Plateau and in surrounding regions. Using the SNP data set, genotype–environment associations and demographic modelling were used to examine local adaptation and genetic divergence between these two species. While morphologically similar, the two Picea species were genetically differentiated in multiple analyses. These species diverged despite continuous gene flow, and their initial divergence was dated back to the late Quaternary. The effective population sizes of both species have expanded since their divergence, as confirmed by niche distribution simulations. A total of 6365 genes were associated with the tested environmental variables; of these, 41 were positively selected in P. asperata and were mainly associated with temperature, while 83 were positively selected in P. crassifolia and were primarily associated with precipitation. These results deepen our understanding of the adaptive divergence and demographic histories of these two spruce species and highlight the importance of genomic data in deciphering the environmental selection underlying Quaternary interspecific divergence.

Nitrogen enrichment alters multiple dimensions of grassland functional stability via changing compositional stability - Qianna Xu; Xian Yang; Jian Song; Jingyi Ru; Jianyang Xia; Shaopeng Wang; Shiqiang Wan; Lin Jiang (Ecology Letters, 2022)
Anthropogenic nutrient enrichment is known to alter the composition and functioning of plant communities. However, how nutrient enrichment influences multiple dimensions of community‐ and ecosystem‐level stability remains poorly understood. Using data from a nitrogen (N) and phosphorus (P) addition experiment in a temperate semi‐arid grassland that experienced a natural drought, we show that N enrichment, not P enrichment, decreased grassland functional and compositional temporal stability, resistance and recovery but increased functional and compositional resilience. Compositional stability and species asynchrony, rather than species diversity, were identified as key determinants of all dimensions of grassland functional stability, except for recovery. Whereas grassland functional recovery was decoupled from compositional recovery, N enrichment altered other dimensions of functional stability primarily through changing their corresponding compositional stability dimensions. Our findings highlight the need to examine ecological stability at the community level for a more mechanistic understanding of ecosystem dynamics in the face of environmental change.

Winter–summer contrast of the 1990s decadal change in relation to Afro–Asian monsoons - Chi-Hua Wu; Pei-Chia Tsai; Wan-Ru Huang; S.-Y. Simon Wang (Climate Dynamics, 2022)

Irisin promotes the proliferation and tenogenic differentiation of rat tendon-derived stem/progenitor cells via activating YAP/TAZ - Langhai Xu; Zhonggai Chen; Tingting Geng; Bin Ru; Quan Wan; Jianbin Zhang; Shun Li; Wenjun Cai (In Vitro Cellular & Developmental Biology - Animal, 2022)
Tendinopathy is a common tendon disorder characterized by pain, swelling, and dysfunction. Current evidence has demonstrated that the depletion of stem cell pool and non-tenogenic differentiation of tendon-derived stem/progenitor cells (TSPCs) might account for the pathogenesis of tendinopathy. FNDC5/Irisin, as a novel exercise-induced myokine, is proved to be involved in the exercise-induced protective effects on musculoskeletal disorders. However, whether irisin can affect TSPCs fate is still unknown. To ascertain the roles of irisin on the proliferation and tenogenic differentiation of TSPCs, rat TSPCs were isolated and incubated with irisin. Cell viability, phenotypic changes, and related signaling pathways were evaluated by CCK-8 assay, colony formation assay, real-time PCR, Western blot, immunofluorescence, and proteasome activity assay. We found that irisin treatment increased the proliferative and colony-forming abilities, and promoted the tenogenic differentiation of TSPCs by upregulating the expression of YAP/TAZ. In conclusion, our work showed for the first time that irisin promotes the proliferation and tenogenic differentiation of rat TSPCs in vitro by activating YAP/TAZ, and the process was associated with a ubiquitin-proteasome proteolytic pathway. In conclusion, irisin and agents targeting YAP/TAZ may be promising therapeutic options for tendinopathy.

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Whole Genome Sequencing and Biological Characteristics of Two Strains of Porcine Escherichia coli Isolated from Saba Pigs - Bo Zhang; Weiwei Zhao; Bin Gao; Chunlan Shan; Xi Wang; Quan Wan; Jing Deng; Jinglong Cha; Bingxun Chen; Dongmei Han; Libo Gao; Pingxing Ao; et al. (Current Microbiology, 2022)

Increased precipitation and nitrogen addition accelerate the temporal increase in soil respiration during 8‐year old‐field grassland succession - Jiajia Zhang; Jingyi Ru; Jian Song; Heng Li; Xiaoming Li; Yafei Ma; Zheng Li; Yuanfeng Hao; Zhensheng Chi; Dafeng Hui; Shiqiang Wan (Global Change Biology, 2022)
Ecological succession after disturbance plays a vital role in influencing ecosystem structure and functioning. However, how global change factors regulate ecosystem carbon (C) cycling in successional plant communities remains largely elusive. As part of an 8‐year (2012–2019) manipulative experiment, this study was designed to examine the responses of soil respiration and its heterotrophic component to simulated increases in precipitation and atmospheric nitrogen (N) deposition in an old‐field grassland undergoing secondary succession. Over the 8‐year experimental period, increased precipitation stimulated soil respiration by 11.6%, but did not affect soil heterotrophic respiration. Nitrogen addition increased both soil respiration (5.1%) and heterotrophic respiration (6.2%). Soil respiration and heterotrophic respiration linearly increased with time in the control plots, resulting from changes in soil moisture and shifts of plant community composition from grass–forb codominance to grass dominance in this old‐field grassland. Compared to the control, increased precipitation significantly strengthened the temporal increase in soil respiration through stimulating belowground net primary productivity. By contrast, N addition accelerated temporal increases in both soil respiration and its heterotrophic component by driving plant community shifts and thus stimulating soil organic C. Our findings indicate that increases in water and N availabilities may accelerate soil C release during old‐field grassland succession and reduce their potential positive impacts on soil C accumulation under future climate change scenarios.

New 40Ar/39Ar and (U-Th)/He dating for the Zhunuo porphyry Cu deposit, Gangdese belt, southern Tibet: implications for pulsed magmatic-hydrothermal processes and ore exhumation and preservation - Xiang Sun; Cheng-Biao Leng; Pete Hollings; Qing-Jie Song; Ru-Yue Li; Xiu-Quan Wan (Mineralium Deposita, 2021)

Study on the crustal stress field of the Tengchong volcanic area using composite focal mechanism method - Shu-zhong Sheng; Yong-ge Wan; Chang-sheng Jiang; Xiao-shan Wang; Shan-shan Liang; Gen-ru Xiao; Xiao-hui Hu (Applied Geophysics, 2021)

Haplotype networks of Phycocalidia tanegashimensis (Bangiales, Rhodophyta) indicate a probable invasion from the South China Sea to Brazil - Wan Zhao; Lei Dong; Dang Diem Hong; Juliet Brodie; Wei-Zhou Chen; Dam Duc Tien; Wei Zhou; Qin-Qin Lu; Mei-Ru Zhang; Li-En Yang (Marine Biodiversity, 2021)

Effects of Grazing, Wind Erosion, and Dust Deposition on Plant Community Composition and Structure in a Temperate Steppe - Mengmei Zheng; Jian Song; Jingyi Ru; Zhenxing Zhou; Mingxing Zhong; Lin Jiang; Dafeng Hui; Shiqiang Wan (Ecosystems, 2021)

Nonadditive and Legacy Effects of Spring and Autumn Warming on Soil Respiration in an Old-Field Grassland - Shijie Ning; Jian Song; Jingyi Ru; Zhenxing Zhou; Jiajia Zhang; Xianghui Liu; Yan Hui; Yafei Ma; Shiqiang Wan (Ecosystems, 2021)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The neural mechanisms of immediate and follow-up of the treatment effect of hypnosis on smoking craving - Xiaoming Li; Lijun Chen; Ru Ma; Haibao Wang; Li Wan; Junjie Bu; Wei Hong; Wanwan Lv; Yihong Yang; Hengyi Rao; Xiaochu Zhang (Brain Imaging and Behavior, 2020)

Comparative Variations of Extractive Nitrogenous Components and Quality in Fresh Muscle and Dried Product of Rabbitfish ( Siganus fuscescens ) in Taiwan - Yu-Ru Huang; Wan-Yi Huang; Hsiao-Chin Jen; Bi-Yu Liu; Ken-Meng Huang; Deng Fwu Hwang (Journal of Aquatic Food Product Technology, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Climatology and change of extreme precipitation events in Taiwan based on weather types - Yi‐chao Wu; S.‐Y. Simon Wang; Yi‐Chiang Yu; Chu‐Ying Kung; An‐Hsiang Wang; Sebastian A. Los; Wan‐Ru Huang (International Journal of Climatology, 2019)
Taiwan's most significant natural hazards are caused by hydrological extremes resulting from excessive precipitation. The threat of extreme precipitation is posed by several different types of weather patterns that affect Taiwan. This study examined the bi‐decadal changes in rainfall by defining an extreme precipitation occurrence (EPO) for a range of event durations from 1 to 24 hr. Three major weather types affecting EPO in Taiwan were identified from 1993 to 2015: the front type consisting of either a frontal zone or convective systems developing with an apparent Meiyu cloudband, diurnal rainfall events when no apparent synoptic features are present, and a tropical cyclone (TC) type according to the maximum sustained wind radius of a TC. Results show that TC‐type events have the greatest overall contribution to EPO at longer (>6 hr) durations. Diurnal/afternoon convection events contribute most to the shorter ( 6 hr) EPO associated with the TC‐type events in summer. The distinction between EPO trends for the entire island of Taiwan and for the Taipei metropolitan area alone (northern Taiwan, population of 7 million) were compared, and an intriguing interannual variation is reported in the TC‐type EPO associated with the TC season 1 year to a year and half just before an El Niño–Southern Oscillation event. The analysis here provides refined statistical distributions of extreme rainfall, and these can contribute to the revision of governmental definitions for weather disasters that are used in mitigation and response strategies.

Asymmetric responses of plant community structure and composition to precipitation variabilities in a semi-arid steppe - Mingxing Zhong; Jian Song; Zhenxing Zhou; Jingyi Ru; Mengmei Zheng; Ying Li; Dafeng Hui; Shiqiang Wan (Oecologia, 2019)

Evaluation of chromatophores as natural marks for delta smelt: the effects of life-stage and light intensity - Gonzalo C. Castillo; Marade E. Sandford; Tien-Chieh Hung; Wan-Ru Yang; Galen Tigan; Luke Ellison; Joan C. Lindberg; Erwin E. Van Nieuwenhuyse (Environmental Biology of Fishes, 2019)

LaMIR166a-mediated auxin biosynthesis and signalling affect somatic embryogenesis in Larix leptolepis - Zhe-Xin Li; Yan-Ru Fan; Shao-Fei Dang; Wan-Feng Li; Li-Wang Qi; Su-ying Han (Molecular Genetics and Genomics, 2018)

Aquatic plant debris changes sediment enzymatic activity and microbial community structure - Wan-Lei Xue; Wei Pan; Qi Lu; Qian-Ru Xu; Cai-Nan Wu; Shao-Ting Du (Environmental Science and Pollution Research, 2018)

Absorption and subcellular distribution of cadmium in tea plant (Camellia sinensis cv. “Shuchazao”) - De-ju Cao; Xun Yang; Geng Geng; Xiao-chun Wan; Ru-xiao Ma; Qian Zhang; Yue-gan Liang (Environmental Science and Pollution Research, 2018)

Characteristics and mechanisms of the diurnal variation of winter precipitation in Taiwan - Wan‐Ru Huang; Ya‐Hui Chang (International Journal of Climatology, 2018)
Using gridded precipitation data remapping from rain‐gauge observations of the time period of 2001–2015 winter months (December, January and February), this study examines the spatio‐temporal characteristics of the climatological diurnal winter precipitation in Taiwan. Our results show that the timings of the maximum values of the diurnal precipitation in Taiwan exhibit clear east–west regional differences, with night‐time maxima over eastern Taiwan but early morning maxima over western Taiwan. Analyses also show that the climatological characteristics of diurnal winter precipitation documented in this study are not controlled by some unusual, heavy precipitation events and can be seen as the common features. By examining the changes in meteorological variables (including winds, relative humidity and temperature) extracted from the in situ observations and the MERRA (Modern‐Era Retrospective Analysis for Research and Applications) reanalysis, this study further suggests that (a) the radiative cooling effect and (b) the surface wind convergence induced by the interaction between the local orography, the local land–sea breeze and the large‐scale diurnal circulation changes over the East Asian–western North Pacific (EAWNP) region are two of the possible formation mechanisms responsible for the spatio‐temporal differences of the climatological diurnal winter precipitation in Taiwan. This finding sheds light on the importance of understanding the role of the large‐scale diurnal circulation changes over the EAWNP region in modulating local diurnal precipitation properties during the winter months.

Impact of boreal summer intra‐seasonal oscillations on warm season diurnal convection activity in Taiwan - Wan‐Ru Huang; Ya‐Hui Chang (International Journal of Climatology, 2018)
Diurnal convection (DC), which is characterized by rainy days with maximum rainfall during the afternoon without strong synoptic disturbances, is the most frequently observed weather system that affects local rainfall in Taiwan. In this study, we investigate the impact of boreal summer intra‐seasonal oscillations (BSISOs) on the modulation of warm season (May–September) DC activities in Taiwan. Our analyses focus on (1) identifying the relationships between changes in DC characteristics (e.g. DC days and the mean rainfall intensities on DC days) and the phase evolutions of two types of BSISOs (including the 30–60‐day ISO named BSISO1 and the 10–30‐day ISO named BSISO2) and (2) the related maintenance mechanisms. Analyses of DC days demonstrate that the contribution of DC days to the total quantity of rainy days in Taiwan generally reaches a maximum value when Taiwan is being modulated by intensified southwesterly winds, intensified local sea breeze circulations, and intensified local thermal instabilities (i.e. phase 3 of BSISO1 and phase 7 of BSISO2). Analyses of the mean rainfall intensities on DC days show that maximum values are generally reached when the moisture convergence line propagates northwards over Taiwan (i.e. phase 1 of BSISO1 and phase 3 of BSISO2). Further examinations indicate that the abovementioned findings are not dependent upon the strengths of the BSISOs.

Decadal fluctuations in the western Pacific recorded by long precipitation records in Taiwan - Wan-Ru Huang; S.-Y. Simon Wang; Biing T. Guan (Climate Dynamics, 2018)

Shifts of growing‐season precipitation peaks decrease soil respiration in a semiarid grassland - Jingyi Ru; Yaqiong Zhou; Dafeng Hui; Mengmei Zheng; Shiqiang Wan (Global Change Biology, 2018)
Changing precipitation regimes could have profound influences on carbon (C) cycle in the biosphere. However, how soil C release from terrestrial ecosystems responds to changing seasonal distribution of precipitation remains unclear. A field experiment was conducted for 4 years (2013–2016) to examine the effects of altered precipitation distributions in the growing season on soil respiration in a temperate steppe in the Mongolian Plateau. Over the 4 years, both advanced and delayed precipitation peaks suppressed soil respiration, and the reductions mainly occurred in August. The decreased soil respiration could be primarily attributable to water stress and subsequently limited plant growth (community cover and belowground net primary productivity) and soil microbial activities in the middle growing season, suggesting that precipitation amount in the middle growing season is more important than that in the early, late, or whole growing seasons in regulating soil C release in grasslands. The observations of the additive effects of advanced and delayed precipitation peaks indicate semiarid grasslands will release less C through soil respiratory processes under the projected seasonal redistribution of precipitation in the future. Our findings highlight the potential role of intra‐annual redistribution of precipitation in regulating ecosystem C cycling in arid and semiarid regions.

Bulk Freeze-Drying Milling: a Versatile Method of Developing Highly Porous Cushioning Excipients for Compacted Multiple-Unit Pellet Systems (MUPS) - Carin Ru Shan Siow; Paul Wan Sia Heng; Lai Wah Chan (AAPS PharmSciTech, 2018)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Future changes in propagating and non-propagating diurnal rainfall over East Asia - Wan-Ru Huang; S.-Y. Simon Wang (Climate Dynamics, 2017)

Removal of Congo red from aqueous solution by adsorption onto different amine compounds modified sugarcane bagasse - Jun-xia Yu; Wan-li Xiong; Jing Zhu; Jia-dong Chen; Ru-an Chi (Clean Technologies and Environmental Policy, 2017)

A Selective Colorimetric and Turn-on Fluorescent Chemosensor for Hg2+ in Aqueous Solution - Yi-Ru Chiou; Chin-Feng Wan; An-Tai Wu (Journal of Fluorescence, 2017)

Invasion genetics of Senecio vulgaris: loss of genetic diversity characterizes the invasion of a selfing annual, despite multiple introductions - Bi-Ru Zhu; Spencer C. H. Barrett; Da-Yong Zhang; Wan-Jin Liao (Biological Invasions, 2017)

Dynamic quantitative proteomics characterization of TNF-α-induced necroptosis - Yang Wang; Zhi-Hao Huang; Yang-Jia Li; Gui-Wei He; Ru-Yuan Yu; Jie Yang; Wan-Ting Liu; Bin Li; Qing-Yu He (Apoptosis, 2016)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

Fast Marching and Runge–Kutta Based Method for Centreline Extraction of Right Coronary Artery in Human Patients - Hengfei Cui; Desheng Wang; Min Wan; Jun-Mei Zhang; Xiaodan Zhao; Ru San Tan; Weimin Huang; Wei Xiong; Yuping Duan; Jiayin Zhou; Tong Luo; Ghassan S. Kassab; et al. (Cardiovascular Engineering and Technology, 2016)

Evaluating the impacts of cumulus, land surface and ocean surface schemes on summertime rainfall simulations over East-to-southeast Asia and the western north Pacific by RegCM4 - Yu-Bin Li; Chi-Yung Tam; Wan-Ru Huang; Kevin K. W. Cheung; Zhiqiu Gao (Climate Dynamics, 2016)

Trends in pre‐summer frontal and diurnal rainfall activities during 1982–2012 over Taiwan and Southeast China: characteristics and possible causes - Wan‐Ru Huang; Kuan‐Chieh Chen (International Journal of Climatology, 2015)

Genetic and serological characterization of chrysanthemum stem necrosis virus, a member of the genus Tospovirus - Pei-Ru Wu; Wan-Chu Chien; Mitsuru Okuda; Minoru Takeshita; Shyi-Dong Yeh; Yun-Chi Wang; Tsung-Chi Chen (Archives of Virology, 2015)

A novel strategy for rapid quantification of 20( S )-protopanaxatriol and 20( S )-protopanaxadiol saponins in Panax notoginseng P. ginseng and P. quinquefolium - Fa-Xiang Xu; Cen Yuan; Jian-Bo Wan; Ru Yan; Hao Hu; Shao-Ping Li; Qing-Wen Zhang (Natural Product Research, 2015)

The role of epithelial tight junctions involved in pathogen infections - Ru-Yi Lu; Wan-Xi Yang; Yan-Jun Hu (Molecular Biology Reports, 2014)

Impact of land–sea breezes at different scales on the diurnal rainfall in Taiwan - Wan-Ru Huang; Shih-Yu Wang (Climate Dynamics, 2014)

Dynamical downscaling forecasts of Western North Pacific tropical cyclone genesis and landfall - Wan-Ru Huang; Johnny C. L. Chan (Climate Dynamics, 2014)

Comparison of the dissipation behaviour of three neonicotinoid insecticides in tea - Ru-Yan Hou; Jin-Feng Hu; Xiao-San Qian; Ting Su; Xiao-Hui Wang; Xiu-Xia Zhao; Xiao-Chun Wan (Food Additives & Contaminants: Part A, 2013)

Culture of amelanotic melanocytes derived from human fetal hair follicles - Ru-zhi Zhang; Wen-yuan Zhu; Hong-zhou Li; Dong-zhang Xue; Cong-jun Jiang; Wan Li (In Vitro Cellular & Developmental Biology - Animal, 2013)

Regional climate simulations of summer diurnal rainfall variations over East Asia and Southeast China - Wan-Ru Huang; Johnny C. L. Chan; Andie Y. M. Au-Yeung (Climate Dynamics, 2013)

Molecular characterization of a gene POLR2H encoded an essential subunit for RNA polymerase II from the Giant Panda (Ailuropoda Melanoleuca) - Yu-jie Du; Yi-ling Hou; Wan-ru Hou (Molecular Biology Reports, 2013)

Co-variability of poleward propagating atmospheric energy with tropical and higher-latitude climate oscillations - Wan-Ru Huang; Tsing-Chang Chen; Shih-Yu Wang (Climate Dynamics, 2012)

Seasonal variation of diurnal and semidiurnal rainfall over Southeast China - Wan-Ru Huang; Johnny C. L. Chan (Climate Dynamics, 2012)

Expression, purification, and evaluation for anticancer activity of ribosomal protein L31 gene (RPL31) from the giant panda (Ailuropoda melanoleuca) - Xiu-Lan Su; Yi-Ling Hou; Xiang-Hui Yan; Xiang Ding; Wan-Ru Hou; Bing Sun; Si-Nan Zhang (Molecular Biology Reports, 2012)

Cloning and overexpression of an important functional gene ATP6V1F encoding a component of vacuolar ATPase from the Giant Panda (Ailuropoda melanoleuca) - Yu-jie Du; Yi-ling Hou; Wan-ru Hou (Molecular Biology Reports, 2012)

Observational and supportive modelling analyses of winter precipitation change in China over the last half century - Robert R. Gillies; Shih‐Yu Wang; Wan‐Ru Huang (International Journal of Climatology, 2012)
Overall increasing trends in annual precipitation and widespread warming over China have been documented. During the winter months in southeast China, where snow is commonplace but rarely accumulates, the climatological 0 °C surface isotherm generally defines the southern boundary of the snowfield. Therefore, a warming climate will: (a) modify the southern boundary of the snowfield; and (b) potentially alter the snow‐rain ratio. Using recently released daily precipitation from the Asian Precipitation‐Highly Resolved Observational Data Integration Towards Evaluation (APHRODITE) and temperature observations from the ERA‐40/Interim Reanalyses, this study investigated historical winter precipitation changes in China. Since snowfall observations were largely unavailable for southeast China, snowfall amounts were estimated using a rain‐snow threshold temperature (RST) method which was subsequently verified by in situ and satellite observations of snow depth, snow cover, and snow water equivalent (SWE). The composite analysis reveals a decrease in snowfall totals which are accompanied by an increase in rainfall; this change corresponds with the northward retreat of the 0 °C surface isotherm and the snow‐rain ratio. Atmospheric circulation analysis indicated lower tropospheric warming with increased moisture over southeast China, consistent with previous studies. Moreover, we observed an increase in the convergence of water vapour flux which sustains the increase in precipitation; this is accompanied by the suppression of snowfall due to the lower tropospheric warming. An additional analysis employed to further substantiate the RST method was undertaken by modelling the snow‐rain ratio with the Weather Research and Forecasting (WRF) Model. The results were in agreement with those estimated from the observations. Copyright © 2011 Royal Meteorological Society

Discrepancies between global reanalyses and observations in the interdecadal variations of Southeast Asian cold surge - Wan‐Ru Huang; Shih‐Yu Wang; Johnny C. L. Chan (International Journal of Climatology, 2011)
The Siberian High (SH) is an important part of the East Asian winter monsoon (EAWM) and is closely linked to cold surges. Previous studies revealed a pronounced decline in the strength of the SH during the late 20th century accompanied with a coherent decrease in the frequency of cold surges. However, studies using different data sets yielded different behaviour of the trends. Here we examine the interdecadal variations of the SH and cold surges deduced from six modern global reanalysis data sets. Discrepancies in such variations are found between the reanalysis data sets and observations as well as among different reanalysis data sets. Such discrepancies contribute to inconsistent interdecadal variations of the cold surge frequency in different reanalysis data sets. Potential causes of this situation are discussed. Copyright © 2010 Royal Meteorological Society

Effect of neuronal excitotoxicity on Munc18-1 distribution in nuclei of rat hippocampal neuron and primary cultured neuron - Yan-Ping Zhang; Ping Wan; Hong-Quan Wang; Hong Zhao; Yu-Xia Xu; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2011)

SR16388: a steroidal antiangiogenic agent with potent inhibitory effect on tumor growth in vivo - Wan-Ru Chao; Khalid Amin; Yihui Shi; Peter Hobbs; Mas Tanabe; Mary Tanga; Ling Jong; Nathan Collins; Richard Peters; Keith Laderoute; Dominic Dinh; Dawn Yean; et al. (Angiogenesis, 2011)

Glutamate enhances the surface distribution and release of Munc18 in cerebral cortical neurons - Ping Wan; Yan-Ping Zhang; Jie Yan; Yu-Xia Xu; Hong-Quan Wang; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2010)

cDNA, genomic sequence cloning and overexpression of ribosomal protein S25 gene (RPS25) from the Giant Panda - Yan-zhe Hao; Wan-ru Hou; Yi-ling Hou; Yu-jie Du; Tian Zhang; Zheng-song Peng (Molecular Biology Reports, 2009)

Transcriptomic adaptations in rice suspension cells under sucrose starvation - Huei-Jing Wang; Ai-Ru Wan; Chia-Mei Hsu; Kuo-Wei Lee; Su-May Yu; Guang-Yuh Jauh (Plant Molecular Biology, 2007)

An efficient protocol for plant regeneration from protoplasts of the moss Atrichum undulatum P. Beauv in vitro - Lin-Hui Li; Xian-Ping Wang; Wan-Ru Hou; Xiang-Lin Liu; Yi-Kun He (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)